The Antiinflammatory Cytokine Interleukin-1 Receptor Antagonist Protects from High-Fat Diet-Induced Hyperglycemia - Sauter, Nadine S. (The Endocrine Society, 2008)
Subclinical inflammation is a recently discovered phenomenon in type 2 diabetes. Elevated cytokines impair β-cell function and survival. A recent clinical trial shows that blocking IL-1β signaling by IL-1 receptor antagonist (IL-1Ra) improves β-cell secretory function in patients with type 2 diabetes. In the present study, we provide further mechanisms of the protective role of IL-1Ra on the β-cell. IL-1Ra prevented diabetes in vivo in C57BL/6J mice fed a high-fat/high-sucrose diet (HFD) for 12 wk; it improved glucose tolerance and insulin secretion. High-fat diet treatment increased serum levels of free fatty acids and of the adipokines resistin and leptin, which were reduced by IL-1Ra treatment. In addition, IL-1Ra counteracted adiponectin levels, which were decreased by high-fat feeding. Studies on isolated islets revealed that IL-1Ra specifically acted on the β-cell. IL-1Ra protected islets from HFD treated animals from β-cell apoptosis, induced β-cell proliferation, and improved glucose-stimulated insulin secretion. Insulin mRNA was reduced in islets from mice fed a HFD but normalized in the IL-1Ra group. Our results show that IL-1Ra improves β-cell survival and function, and support the potential role for IL-1Ra in the treatment of diabetes.